Characterization of cellular heterogeneity in milk from healthy bovine mammary glands - Gabriela Perez-Hernandez; Andrea J. Lengi; Melissa Makris; Benjamin A. Corl (Animal Nutriomics)
Somatic cells (SCs) in milk are a heterogeneous population composed of several subsets of cells. However, a complete understanding of this heterogeneity in cow’s milk remains elusive. This study aimed to characterize heterogeneity within mammary epithelial (MEC) and immune cell subpopulations from healthy Holstein cows. An initial cell characterization of SC populations was completed using a single milk collection (3.8 L) from a base population of 25 multiparous Holstein cows to identify MEC and immune cells using flow cytometry with Butyrophilin 1A1 (BTN) and CD45 as cell surface markers. From the base population, 5 multiparous cows (≥300 days in milk (DIM), ≤162 × 103 SC/mL, and milk yield (MY) ≥ 25 kg/d) were selected for fluorescence activated cell sorting and single-cell RNA sequencing (scRNA-seq) analysis. A single-cell-suspension of approximately 1,000 sorted cells was prepared from each cow for characterization using scRNA-seq. Gel beads and barcodes were generated, cDNA amplified, cDNA sequencing libraries constructed and sequenced. After data normalization, scaling, and filtering control, two CD45+ databases were generated. The CD45+ databases contained 923 and 851 single cells, each comprising 17,771 and 12,156 features, respectively. Principal component analysis revealed seven and eight distinguishing clusters. Based on marker expression, most immune cells present in the samples were T cells (CD3E and PTPRC). Three different T cell subpopulations were revealed: helpers (CD4), cytotoxic (CD8A and CD8B), and regulatory T cells (IL2RA). The remaining four clusters were composed of granulocytes (neutrophils, eosinophils, and basophils; TLR4 and CXCL8), macrophages (PTPRC, CD14, CD68, TL2, IL1B), and a small population of B cells (CD19, CD22, and MS4A1). The study and characterization of immune cell subpopulations present in milk provide a basis for developing greater insights into mammary gland immune function, offering potential avenues for enhancing animal health and milk production in the future.